2020
DOI: 10.1099/mgen.0.000381
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution in the major outer membrane protein OmpA of Acinetobacter baumannii

Abstract: Acinetobacter baumannii is nowadays a relevant nosocomial pathogen characterized by multidrug resistance (MDR) and concomitant difficulties to treat in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 68 publications
(158 reference statements)
0
15
0
Order By: Relevance
“…However, the increase in antibiotic-susceptibility of these mutants could be related to a broader membrane permeability as a consequence of membrane alterations [ 61 ]. Nevertheless, several studies demonstrated that OmpA acts as a specific and selective channel for small antibiotics [ 41 , 61 , 62 , 124 ]. However, multiple data indicate that OmpA is associated with efflux pump systems located in the inner membrane to counteract the influx of antibiotics [ 62 ].…”
Section: A Baumannii and The Treasure Of Its Virulomementioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase in antibiotic-susceptibility of these mutants could be related to a broader membrane permeability as a consequence of membrane alterations [ 61 ]. Nevertheless, several studies demonstrated that OmpA acts as a specific and selective channel for small antibiotics [ 41 , 61 , 62 , 124 ]. However, multiple data indicate that OmpA is associated with efflux pump systems located in the inner membrane to counteract the influx of antibiotics [ 62 ].…”
Section: A Baumannii and The Treasure Of Its Virulomementioning
confidence: 99%
“…Due to its key role, several proteins control ompA expression such as the global repressor H-NS and an anti-repressor (i.e., gene locus A1S_0316), the RNA chaperone Hfq as well as the two-component system BfmSR [ 41 , 125 , 126 ]. Its high amino acid conservation among isolates, crucial structural role and strong immunogenicity make OmpA the ideal target for the development of an A. baumannii vaccine [ 124 ]. Additionally, several studies have addressed the role of CarO or carbapenem susceptibility porin in A. baumannii [ 13 , 41 , 68 , 69 , 70 ].…”
Section: A Baumannii and The Treasure Of Its Virulomementioning
confidence: 99%
“…The annotated protein referred to as WP_166170865 consists of three distinct domains, including an N-terminal signal peptide, a β-barrel, and an OmpA-like domain at the C terminus. The β-barrel domain of SA01-OmpA, like its homologs in other Acinetobacter ( 31 ), consists of eight β-strands connected with four periplasmic inner loops and four outer membrane loops ( Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…The genomic diversity among Acinetobacter strains and their adaptive evolution can cause physiological variations among them ( 30 ). Moreover, there are different variants of OmpA (with potentially different physicochemical properties) in the Acinetobacter population, which might be due to the lateral gene transfer ( 31 ). Therefore, the entire genome of Acinetobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“… 68 , 69 , 70 , 71 Polymorphism of OmpA that resulted in five major bacterium variants, however, may limit the effectiveness of vaccine from a single OmpA variant. 72 In addition to OmpA, other OMPs that have been evaluated for their potential as vaccine candidates are Omp22 73 and BamA. 74 These target proteins have been demonstrated as highly conserved among the A. baumannii strains (95–99%) and displayed promising potential for active and passive immunization.…”
Section: Progress In a Baumannii Vaccine Developmentmentioning
confidence: 99%